INDONESIAN EFL TEACHERS STUDYING OVERSEAS: FEELINGS, EXPECTATIONS, AND PERSPECTIVES ON PROFESSIONAL DEVELOPMENT - Bambang Yudi Cahyono (Soegijapranata Catholic University, 2013)
One of the ways to develop English teachers' professional competence is by sending them to study in a graduate program in English language education. Sending English teachers to pursue their higher level of education is one of the policies taken by the Government of East Java to improve English teachers' professional competence. In response to the Government of East Java's policy, teachers were selected to study in a graduate program with a sandwich study. The sandwich takes the format of